Electrical and thermal properties of polyurethane/carbon nanotubes composites - Vilas Boas, H. M. (2011)
The aim of this work was to study the effect of dispersing small amounts of CNT on the thermal diffusivity and electrical resistivity of PU/CNT composites. The PU nanocomposites were prepared with 0.5% and 1% weight of CNT. The composites were prepared by dispersion of the CNT in poly(propylene glycol) (PPG) followed by in situ polymerization, by mixing with 4,4′-Methylene di-p-phenyl diisocyanate (MDI). The PPG was characterized by an average molecular weight of 425 g/mol and a hydroxyl value 250 to 276 mg KOH/g. The MDI was characterized by a isocianate value (%NCO value) of 27.9-29.2. It was observed that the thermal diffusivity slightly increased with the addition of the CNT, but the results obtained were within the typical range for polymers (in the order of 10-8 m2/s). The electrical resistivity measured for the composites showed a large decrease after the addition of 0.5% and 1% of CNT. The electrical resistivity decreased 3 and 7 decades (from 109 .m to 106 and 103 .m) for 0.5 and 1% CNT composites, respectively. Thus, the composite bearing 1% of CNT dispersed in the PU presented semiconductor behaviour.